The vehicle routing problem for perishable goods: A systematic review. Issue 1 (1st January 2020) - Utama, Dana Marsetiya; Dewi, Shanty Kusuma; Wahid, Abdul; Santoso, Imam
Abstract: Vehicle Routing Problem (VRP) is the problem for finding optimal routes in the distribution system, and this problem needs attention because it can improve distribution performance. One of the problems in VRP is the Vehicle Routing Problem for Perishable Goods (VRPfPG). This issue addresses VRP for products that are rapidly losing quality and perishable. This paper attempts to review the Vehicle Routing Problem for Perishable Goods (VRPfPG). A systematic review has been carried out on fifty-nine (59) published papers from 2001 to March 2020. The optimization methods in this review were classified into single and multi-objective problems. In addition, the review was also conducted based on the objective function. The results show the metaheuristic algorithm to be a popular optimization method for solving single and multi-objective problems. Further, the results also show that minimizing the total cost distribution to be the objective function that was often used by researchers. Finally, future studies are suggested to explore a more comprehensive investigation in the VRPfPG.